Postoperative complications associated with different fixation methods of isolated mandibular angle fractures - Ferreira E Costa, Rafael [UNESP]; Oliveira, Marina Reis [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Pereira-Filho, Valfrido Antônio [UNESP]; Vieira, Eduardo Hochuli [UNESP] (Wolters Kluwer, 2018)
The objective of this study was to review the medical records of patients with a history of mandibular angle fracture who were attended at the Service of Oral and Maxillofacial Surgery and Traumatology of FOAr/UNESP in the last 5 years. The data collected were subjected to chi-squared test (significance level of 5%). The authors reviewed 19 medical records. The main cause was physical aggression (58.00%), but with no statistical difference in relation to the other etiologies (P>0.05). Regarding the type of fixation, one 2.0-mm system plate associated with one 2.4-mm system plate and the fixation using only two 2.0-mm system plates were used in 7 patients each. The fixation method with a monocortical plate at the upper border was used in 5 patients. However, there was no statistically significant difference in the frequency of complications among the 3 fixation methods used (P>0.05). In 52.64% of the patients, the third molar was removed intraoperatively. Despite this, there was no statistically significant difference in the frequency of complications when the third molar was in the fracture line or when it was removed postoperatively (P>0.05). The complications observed were dehiscence associated with pain (44.44%), trismus (22.22%), infection (22.22%), and presence of bone spicules (11.11%). However, no statistical differenceswere observed between the frequency of different types of complications (P=0.779). In the sample studied, there were no differences in the frequency of complications among the fixation methods applied.
Keywords: Mandible; Mandibular trauma; Postoperative complications; Rigid internal fixation